Pre-School Age Visually Impaired Children’s Motives for Learning - Gudonis, Vytautas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article presents longitudinal data of the survey of 212 Šiauliai Petras Avižonis Visual Centre’s 6–7-year-old pre-school children’s motives to attend school. A brief theoretical analysis of significance of motives for learning in child’s development is displayed. Analysing research results, a positive experience on development of positive motives for school attendance in pre-school age children attending Šiauliai Petras Avižonis Visual Centre is rendered in a generalising way.